ANALISIS MISKONSEPSI SISWA PADA MATERI EKSPONEN BERDASARKAN KEMAMPUAN MATEMATIKA SISWA - Azmi, Hafizatul; Gadih Ranti, Mayang (Koordinat Jurnal MIPA, 2024)
Mathematics consists of concepts that are systematically structured where concepts are interrelated. The ability of the student to understand concepts also greatly affects the learning process of teaching them. One of the obstacles to embedding mathematical concepts is that not all students can understand the concepts well. Students often experience an understanding of concepts that deviate from the concepts of scientists. (miskonsepsi). This study aims to analyze the types and causes of misconceptions on exponent material in class X MAN 2 Hulu Middle River. This research approach uses qualitative research with types of descriptive research. Subject selection based on students' high, medium, and low abilities. Data collection techniques are done with tests, interviews, and documentation. The phases of data analysis according to Milles and Huberman are data reduction, data presentation, and conclusion drawing. As for data validity testing using triangulation techniques. The results of misconception analysis in class X MAN 2 Hulu Sungai Tengah on the exponent material pointed out that the misconception type of high-skilled students suffer from misconcept type of rule error, the skilled students are suffering from sign and letter-understanding malconceptions, and the students with low literacy suffer generalization, sign, rule mistake, and letter understanding malconception. The causes of misconceptions that occur in exponent material are misguided intuitive thinking, incomplete reasoning, and low student learning ability and interest